Through the Boundaries: Environmental Factors Affecting Reef Benthic Cover in Marine Protected Areas in the Philippines - Panga, Fleurdeliz M.; Anticamara, Jonathan A.; Quibilan, Miledel Christine C.; Atrigenio, Michael P.; Aliño, Porfirio M. (Frontiers in Marine Science, 2021)
Philippine coral reefs have been on the decline since the 1970s, and this degradation has posed a risk to biodiversity, food security, and livelihood in the country. In an effort to arrest this degradation, marine protected areas (MPAs) were established across the country. MPAs are known to improve fish biomass, but their effect on live coral cover and other benthos is not yet well documented and understood. In this study, 28 MPAs across the Philippines were surveyed comparing benthic cover and indices between protected reefs and adjacent unprotected reefs. No consistent differences were found between reefs inside and outside MPAs through all the benthic categories and reef health indices considered that are indicative of protection effects or recovery within MPAs. However, there were notable site-specific differences in benthic cover across the study MPAs-suggesting that factors other than protection play important roles in influencing benthic cover inside and outside of MPAs. Storm frequency and proximity to rivers, as a proxy for siltation, were the strongest negative correlates to live coral cover. Also, high coastal population, a proxy for pollution, and occurrence of blast and poison fishing positively correlated with high dead coral cover. The lack of significant difference in benthic cover between reefs inside and outside MPAs suggests that protection does not necessarily guarantee immediate improvement in benthic condition. Correlations between benthic condition and storm frequency, siltation, and pollution suggest that it is necessary to augment MPAs with other management strategies that will address the multiple stressors that are usually indiscriminate of MPA boundaries. Supplementing long-term and systematic monitoring of benthic cover and biodiversity inside and outside of MPAs with data on other important environmental and human impact variables will help improve understanding of benthic cover and biodiversity dynamics inside and outside of MPA boundaries.